2020
DOI: 10.1128/jb.00700-19
|View full text |Cite
|
Sign up to set email alerts
|

Interdependency of Respiratory Metabolism and Phenazine-Associated Physiology in Pseudomonas aeruginosa PA14

Abstract: Extracellular electron transfer (EET), the reduction of compounds that shuttle electrons to distal oxidants, can support bacterial survival when preferred oxidants are not directly accessible. EET has been shown to contribute to virulence in some pathogenic organisms and is required for current generation in mediator-based fuel cells. In several species, components of the electron transport chain (ETC) have been implicated in electron shuttle reduction, raising the question of how shuttling-based metabolism is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 60 publications
3
46
0
Order By: Relevance
“…The respiratory chain of P. aeruginosa includes several dehydrogenases, the cytochrome bc 1 complex, and five terminal oxidases that operate at different concentrations of oxygen, as well as alternative electron acceptors that operate under anaerobic conditions [9]. It has been shown that this bacterium selectively expresses different respiratory enzymes/pathways depending on the availability of nutrients, oxygen, and other electron acceptors [10][11][12][13][14]. Such adaptations are important for colonization of infection sites, particularly in the lungs of patients suffering CF, where the bacteria are challenged with low nutrient and oxygen availability [5].…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory chain of P. aeruginosa includes several dehydrogenases, the cytochrome bc 1 complex, and five terminal oxidases that operate at different concentrations of oxygen, as well as alternative electron acceptors that operate under anaerobic conditions [9]. It has been shown that this bacterium selectively expresses different respiratory enzymes/pathways depending on the availability of nutrients, oxygen, and other electron acceptors [10][11][12][13][14]. Such adaptations are important for colonization of infection sites, particularly in the lungs of patients suffering CF, where the bacteria are challenged with low nutrient and oxygen availability [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore possible that, in the oxic zone at 12 h, cells in SCFM are more protected from PYO toxicity than in LB at 24 h due to a higher electron donor:electron acceptor ratio (41). Finally, the ratios and production of different phenazines (e.g., PYO, PCA, PCN) in P. aeruginosa are known to vary depending on the carbon source in the growth medium (43); such variation could also contribute to the differences that we observed in PodA effects between our media.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches can allow cells to produce electrical current or consume it, resulting in either oxidation or reduction of intracellular redox species, respectively. Bioelectrochemical devices can then be used to drive biosynthetic reactions 1,4,5 , perform bioelectronic sensing 9 , actuate gene expression 3 , and modulate cellular growth 10,11 within the microorganism of interest. Despite these accomplishments, these strategies couple the redox state of the electrode to multiple intracellular redox biomolecules, resulting in off-target effects, cellular toxicity, and poor control of biosynthesis 1,3,4 .…”
Section: Figurementioning
confidence: 99%